2016
DOI: 10.1111/icad.12152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of established shrub shelterbelts around oases on the diversity of ground beetles in arid ecosystems of Northwestern China

Abstract: Oases in arid regions of northwestern China are main sites for agriculture and human settlement. Conservation of these important oasis habitats involves establishing shrub shelterbelts around the oases. We investigated how different types of shrub shelterbelts affect the diversity of ground beetles. We sampled carabid and tenebrionid assemblages with pitfall traps in spring and summer and measured key environmental variables in four habitats of the arid region: planted stands of pure and mixed plantations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Aldryhim et al (1992) found that cultivated area has lower tenebrionids abundance than uncultivated one. Li et al (2016) noted that the beetle community is largely determined by plant cover and diversity. Similar results were observed during the current study whereas the beetle abundance and density were impacted by plant diversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aldryhim et al (1992) found that cultivated area has lower tenebrionids abundance than uncultivated one. Li et al (2016) noted that the beetle community is largely determined by plant cover and diversity. Similar results were observed during the current study whereas the beetle abundance and density were impacted by plant diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Plant groves may be the reason for the relatively low diversity of tenebrionid beetles in the investigated sites. Li et al (2016) concluded that shrub plantations reduce beetle diversity. Many research illustrated that the main cause of reducing the biodiversity of many terrestrial ecosystem is the changes in the land use/ cover (Garnier et al, 2006;Krauss et al, 2010;Garcia-Tejero et al, 2013;Vergnes et al, 2014;Sweaney et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several aspects make desert tenebrionids excellent model organisms for the study of ensemble ecology. First, tenebrionids are abundant and fairly easy to sample by pitfall traps, which makes it possible to obtain sufficiently large samples of individuals in a short time and even from very small sampling areas [21][22][23][24], thus ensuring that the sampled species belong to the same spatial and temporal assemblage. Second, desert tenebrionids are detritivorous and opportunistic animals [18,25], which therefore use the same basic resources.…”
Section: Introductionmentioning
confidence: 99%
“…A full understanding of the wind flow characteristics is essential to arranging the patterns of sand-fixing and windbreak forests. The effects and aerodynamics of sand-fixing and windbreak forests or artificial fences have been persistently investigated through field observations (see Schwartz et al, 1995;Mohammed et al, 1996;Wilson, 2004;Tuzet and Wilson, 2007;Amichev et al, 2015;Li et al, 2016), wind tunnel experiments (see Schwartz et al, 1995;Judd et al, 1996;Lee et al, 2002) and theoretical analyses (see Zhu and Zhou, 1993;Cleugh, 1998;Takahashi et al, 1998;Ucar and Hall, 2001;Amichev et al, 2015). It should be stressed that field observation has been the most frequently used method because of its readiness.…”
Section: Introductionmentioning
confidence: 99%